Congestion Aware Objects Filtering for Collective Perception - Delooz, Quentin; Festag, Andreas; Vinel, Alexey (Electronic Communications of the EASST, 2021)
This paper addresses collective perception for connected and automated driving. It proposes the adaptation of filtering rules based on the currently available channel resources, referred to as Enhanced DCC-Aware Filtering (EDAF).